Diversidade e inclusão : histórias de vida de pessoas com deficiência visual acerca do sentido do trabalho - Castro, Luiz Guilherme Meirelles (2025)
Based on the principles of people management and work relationships with diversity in the organizational context, this study's main objective was to analyze inclusion and the meaning of work for people with visual impairments. Following the theoretical framework of the dimensions model based on Estelle Morin's (2001) methodology, it investigated the meaning of work for people with visual impairments across three dimensions: individual, organizational, and social. Furthermore, it identified the importance of inclusion and participation of people with visual impairments in the labor market and examined the relationship between the feeling of inclusion in the workplace of people with visual impairments and the possible relationship with the meaning of work for them. To conduct this research, the methodological procedures followed a qualitative, exploratory, and descriptive approach. Furthermore, according to Merriam (1998), the research was characterized as a basic qualitative study. In this research, life history was used not only as a data collection technique but also as a qualitative research strategy. This led the researcher to conduct research considering subjectivity, unpredictability, and human complexity, allowing participants to explore subjective realities and valuable insights into the reasons behind their feelings and behaviors at work. Eleven visually impaired individuals living in the northwest region of Rio Grande do Sul were interviewed. To reach this number, snowball and data saturation techniques were used when the interviews no longer yielded new or relevant information, reaching a point of repetition or convergence in the results. Thus, based on a context in which participants felt comfortable speaking, the trigger question was answered: "Based on your life story, what was your insertion into the job market like, and how did it make sense to you?" Using data analysis and interpretation, which followed Bardin's (2011) content analysis, it was possible to glimpse the difficulties faced by visually impaired individuals and their positioning in the workplace. Thus, it can be concluded that all dimensions (individual, organizational, and social) are interconnected, and some people, for individual reasons, may relate one aspect more than another. However, considering the overall context, the analyzed aspects of all dimensions are present and crucial in understanding the meaning of work for people with visual impairments. Furthermore, the association between pay and work was unanimous. Work is undoubtedly a source of survival, but it is not only that; the human factor is also present, and work enables experiences that aid insertion and inclusion. Thus, the research also showed that not only the development of personal, organizational, or social factors will enable the finding of meaning in work, but rather the sum of the characteristics found in all dimensions of analysis, enabling a more informed understanding of the topic. Therefore, it is possible to affirm that this research contributes practically and theoretically to existing studies in the field of administration and people management. In this sense, it has a social impact and allows for a broader view of the difficulties and positioning in the world of work and in the lives of people with visual impairments. Furthermore, it encourages the reader to self-reflect on all the subjectivity that marks the participation of diversities in organizations and regarding the creation and maintenance of effective public policies in the search for the insertion and inclusion of minorities, especially the visually impaired.